About the article entitled “Bioethics and digital environment: current challenges in medical education” - Castillo Castro, Gladys Paulina (2025)
Dear Editor: Having read the article by Luis Yushimito Rubiños in the latest volume of the journal (2024-4)—which addresses a critical issue in medical education: the integration of bioethics into digital environments and the rise of new forms of academic fraud driven by technology misuse—we find it relevant to reflect on the ethical challenges this transformation entails. Given the rapid pace of technological change, ongoing vigilance is essential to safeguard academic integrity.